2006
DOI: 10.2136/vzj2005.0151
|View full text |Cite
|
Sign up to set email alerts
|

Colloid‐Facilitated Solute Transport in Variably Saturated Porous Media: Numerical Model and Experimental Verification

Abstract: Strongly sorbing chemicals (e.g., heavy metals, radionuclides, pharmaceuticals, and explosives) in porous media are associated predominantly with the solid phase, which is commonly assumed to be stationary. However, recent field‐ and laboratory‐scale observations have shown that in the presence of mobile colloidal particles (e.g., microbes, humic substances, clays, and metal oxides), colloids can act as pollutant carriers and thus provide a rapid transport pathway for strongly sorbing contaminants. To address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(102 citation statements)
references
References 73 publications
(119 reference statements)
1
99
0
2
Order By: Relevance
“…To investigate the fate of colloid-associated pollutants, various three-phase transport models (Simunek et al, 2006), including the nonreactive colloids with the solid phase model, the first-order kinetic attachment of colloids model, the irreversible nonlinear kinetic attachment of colloids model, and the Langmuir kinetics attachment of colloids model, have been developed to delineate the pollutant transport in the presence of colloids (Grolimund and Borkovec, 2005;Grolimund et al, 1996;Saiers, 2002;Saiers and Hornberger, 1996;Simunek et al, 2006;Zou and Zheng, 2013). A model, only considering the colloid as a carrier, simulated kaolinite colloid-facilitated 137 Cs transport, but calculated data greatly deviated from the observed data obtained in experiments (Saiers and Hornberger, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the fate of colloid-associated pollutants, various three-phase transport models (Simunek et al, 2006), including the nonreactive colloids with the solid phase model, the first-order kinetic attachment of colloids model, the irreversible nonlinear kinetic attachment of colloids model, and the Langmuir kinetics attachment of colloids model, have been developed to delineate the pollutant transport in the presence of colloids (Grolimund and Borkovec, 2005;Grolimund et al, 1996;Saiers, 2002;Saiers and Hornberger, 1996;Simunek et al, 2006;Zou and Zheng, 2013). A model, only considering the colloid as a carrier, simulated kaolinite colloid-facilitated 137 Cs transport, but calculated data greatly deviated from the observed data obtained in experiments (Saiers and Hornberger, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…. Therefore, according to the reported results, the motion of suspended particles and subsequent colloid-facilitated contaminant transport could provide an additional pathway for the transport of inorganic contaminants (Morales 2011;Simunek et al 2006;Sun et al 2010).…”
Section: Introductionmentioning
confidence: 93%
“…Groundwater contamination due to the spread of various chemical compounds, such as heavy metals, poisonous materials, and agricultural and industrial wastes, has been widely reported in the literature (Esmaeili Bidhendi et al 2010;Lee and Jones 1993;Nouri et al 2008;Simunek et al 2006). The major mechanisms controlling the transport of contaminants may differ in the vadose and saturated zones (Sen and Khilar 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[31] When soil erosion occurs, pharmaceuticals can potentially be transported with the soil colloids in addition to water based transport thus increasing the total pharmaceutical loss. [33][34][35] However, colloid-associated transport depends on the chemistry of the specific compound, the soil type, and irrigation conditions. While studied pharmaceuticals were demonstrated to sorb strongly with particulate matter, their colloid-associated transport is limited by the absolute amount of colloids that can be carried with the water flow.…”
Section: Effect Of Irrigation Ratementioning
confidence: 99%